Aplikasi Pengenalan Nama-nama Hewan - Agus Darmawan (SAP (Susunan Artikel Pendidikan), 2019)
The emergence of technology has shown a significant impact on changing human patterns. Whether it's a negative or positive impact on the use of smartphones. Judging from the impact of using a smartphone, it turns out to have a positive effect if used as a learning medium. A combination of technology and new learning media that are needed by kindergarten schools that can help teachers deliver material on vocabulary to know the names of animals. In designing learning media applications to know the names of animals created using the method of working with waterfall and assisted with the java android programming language with the target output that will be achieved from this design is a prototype in the form of an application to recognize the names of animals in the form of learning media in TK NEGERI JAGAKARSA 01 Android-based. With this application, it is expected to be able to assist teachers in utilizing learning media to improve students' ability to absorb material given by the teacher.